P.Porto research workshops - Dias, André (2019)
P.PORTO Research Workshops are thematic meetings, to present and discuss R&D activities and outcomes – be it in the form of new knowledge, applied technology, industrial or intellectual property – providing a space for debate, networking and creation of synergies. This volume provides the contributions of the Research Workshop of April 2019, dedicated to the set of R&D projects led by P.PORTO researchers, in collaboration with companies and end-users, in the scope of the national projects call 02/SAICT/2016.